2004
DOI: 10.1007/s00468-004-0364-5
|View full text |Cite
|
Sign up to set email alerts
|

Bud burst in Norway spruce (Picea abies): preliminary evidence for age-specific rest patterns

Abstract: This study examines the effect of chilling and photoperiod on rest completion and bud burst in Norway spruce [Picea abies (L.) Karst.] using twigs from both 15-year-old ("young trees") and 56-year-old ("old trees") trees. The material was transferred between September and May from outdoors to experimental forcing conditions with four different photoperiods. The bud burst percentage of the twigs from young trees generally increased in all photoperiods until the end of the year. After that it decreased until ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 32 publications
2
15
2
Order By: Relevance
“…Thus Linkosalo et al's (2006) hypothesis does not provide an adequate solution to the paradox (Table 3.5). Partanen et al (2005) found that the pattern of bud burst percentage, BB%, obtained with 15-year-old Norway spruce trees was different from both the typical pattern observed earlier with seedlings and the other pattern observed by Partanen et al (2005) with older trees. The BB% of the 15-year-old trees first increased in autumn, basically similarly to that observed with seedlings ( Fig.…”
Section: Attempts To Resolve the Paradoxcontrasting
confidence: 48%
See 2 more Smart Citations
“…Thus Linkosalo et al's (2006) hypothesis does not provide an adequate solution to the paradox (Table 3.5). Partanen et al (2005) found that the pattern of bud burst percentage, BB%, obtained with 15-year-old Norway spruce trees was different from both the typical pattern observed earlier with seedlings and the other pattern observed by Partanen et al (2005) with older trees. The BB% of the 15-year-old trees first increased in autumn, basically similarly to that observed with seedlings ( Fig.…”
Section: Attempts To Resolve the Paradoxcontrasting
confidence: 48%
“…3.20). These deviant findings obtained with differentially aged trees led Partanen et al (2005) to hypothesize that the environmental regulation of rest break and bud burst changes as the trees get older. This hypothesis is physiologically motivated, since several aspects of the seasonality of trees change with ageing (Ununger et al 1988;Vitasse 2013).…”
Section: Attempts To Resolve the Paradoxmentioning
confidence: 96%
See 1 more Smart Citation
“…Various studies have shown an interaction between photoperiod and duration of exposure to chilling conditions on budburst timing (Heide 1993, Myking & Heide 1995, Partanen et al 2005, in which LDs promoted growth in birch after partial chilling exposure. Myking & Heide (1995) hypothesised that LDs acted as a substitute for chilling in partially chilled plants.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in addition to young seedlings, branches detached from the trees have been commonly used in forcing experiments. Partanen et al (2005) for instance found that the bud burst percentage of detached twigs of Norway spruce trees varies during winter, and depends on the age of the tree. However, detaching the twig may affect its physiology.…”
Section: Introductionmentioning
confidence: 99%